Effects of Ubiquinol-10 on MicroRNA-146a Expression In Vitro and In Vivo. (16th April 2009) - Schmelzer, Constance; Kitano, Mitsuaki; Rimbach, Gerald; Niklowitz, Petra; Menke, Thomas; Hosoe, Kazunori; Döring, Frank
Abstract : MicroRNAs (miRs) are involved in key biological processes via suppression of gene expression at posttranscriptional levels. According to their superior functions, subtle modulation of miR expression by certain compounds or nutrients is desirable under particular conditions. Bacterial lipopolysaccharide (LPS) induces a reactive oxygen species-/NF-κB-dependent pathway which increases the expression of the anti-inflammatory miR-146a. We hypothesized that this induction could be modulated by the antioxidant ubiquinol-10. Preincubation of human monocytic THP-1 cells with ubiquinol-10 reduced the LPS-induced expression level of miR-146a to 78.9 ± 13.22%. In liver samples of mice injected with LPS, supplementation with ubiquinol-10 leads to a reduction of LPS-induced miR-146a expression to 78.12 ± 21.25%. From these consistent in vitro and in vivo data, we conclude that ubiquinol-10 may fine-tune the inflammatory response via moderate reduction of miR-146a expression.